Factors that can influence the retention of nurse educators in CHAM nursing education institutions - Muzombwe, Mary (Kamuzu University of Health Sciences, 2022)
This report presents findings of the study on Factors that can influence retention of nurse educators in CHAM nursing education institutions. The study was conducted at Mulanje Mission College of Nursing and Midwifery and QECH. A purposive sampling was done in which 10 nurse educators, the college principal and 4 nurse educators who left CHAM nursing colleges and are working in government hospitals were recruited making a total of 15 participants. The study relied on descriptive quantitative method in which data was collected through self administered questionnaire, analysed using frequencies and percentage and presented using tables, Bar graphs and charts. Results indicated that monetary and non-monetary incentives, recognition and promotion, working conditions, location of CHAM nursing institution and leadership and administration are some of the factors necessary for retention of nurse educators in CHAM nursing education institution, with monetary incentive ranking high. The study concludes that there is need to review staff retention strategies in all CHAM nursing education institutions.